In-situ self-cleaning cathode monatomic iron-carbon-based electroactive film, and preparation method and application thereof

CN121317973BActive Publication Date: 2026-10-09BEIJING ACADEMY OF AGRICULTURE & FORESTRY SCIENCES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511730029.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-24
Publication Date
2026-10-09
Estimated Expiration
2045-11-24

AI Technical Summary

Technical Problem

但是该单原子膜制备流程复杂,增加工艺成本

Benefits of technology

1、采用本发明提供的单原子铁碳基电活性膜为阴极,在连续流模式下运行,无需添加任何化学试剂,即可在电场辅助下原位电产生活性氧物种,强化水体中溶解氧气向活性氧物种转化的还原能力,进而实现有机污染物的原位矿化去除,对典型腐殖酸(HA)和蛋白质(BSA)类有机污染物的矿化率达到69.16%和68.78%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121317973B_ABST
    Figure CN121317973B_ABST
Patent Text Reader

Abstract

The application discloses an in-situ self-cleaning cathode monatomic iron-carbon-based electroactive film and a preparation method and application thereof. The electroactive film provided by the application comprises the following components: a film substrate and an electroactive layer loaded on the surface of the film substrate; the electroactive layer is a film layer prepared by pyrolysis-acid washing reaction with a metal organic framework material and a phosphorus-containing source organic reagent as precursors; and the electroactive layer has electron-rich active sites with a micro single-atomic iron coordination environment on the surface. The electroactive film is used as a cathode, and the reduction ability of the electroactive film to convert dissolved oxygen in water into active oxygen species is strengthened under the assistance of an electric field, so that in-situ removal of organic pollutants is realized. Meanwhile, the deposition of negatively charged organic matters in water is inhibited through electrostatic repulsion, which is beneficial to relieving the formation of a pollution layer, realizes the in-situ self-cleaning function of the electroactive film, and has a wide application prospect in the field of sewage treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wastewater treatment technology, specifically relating to an in-situ self-cleaning cathode single-atom iron-carbon-based electroactive membrane, its preparation method, and its application. Background Technology

[0002] Traditional membrane technology has become one of the most energy-efficient and economical water treatment technologies for selective separation, purification, and water treatment. Different membrane processes, such as ultrafiltration, nanofiltration, and reverse osmosis, are currently widely used in wastewater treatment and seawater desalination. However, during wastewater treatment, contaminants gradually accumulate on the membrane surface, clogging the pores and significantly reducing membrane flux, further decreasing treatment efficiency and ultimately shortening membrane lifespan. When membranes are severely fouled, physical and / or chemical cleaning is necessary, inevitably leading to higher operating costs. Therefore, improving membrane antifouling performance, extending cleaning cycles, and slowing flux decline are key issues for improving membrane operating efficiency.

[0003] Cathodic electroactive membrane water treatment technology is a typical flow-type electrochemical advanced oxidation process that combines electro-Fenton oxidation with membrane separation technology, emerging in recent years. The electro-Fenton oxidation process aims to generate and activate hydrogen peroxide in situ, decomposing it into highly reactive oxygen species to effectively oxidize and remove small-molecule organic matter. Simultaneously, the synergistic membrane separation technology not only enhances the convective mass transfer effect at the electrode interface, achieving contaminant concentration enrichment at the membrane interface and accelerating the pollutant degradation kinetics, but also enables self-cleaning of the membrane interface under the assistance of an electric field, controlling the formation of a fouling layer and extending the membrane's service life. Therefore, the aforementioned cathodic electroactive membrane water treatment technology is considered to have broad application prospects in the field of water treatment.

[0004] In existing technologies, patent CN115784363A synthesizes a micro / nano-scale material with light absorption capabilities and the ability to activate persulfate. This material is uniformly and stably fixed onto the membrane surface using surface loading technology, forming a self-cleaning membrane. This self-cleaning membrane, when persulfate solution is added under visible light, degrades pollutants in situ. However, this method requires the addition of a certain concentration of chemical agents, posing a risk to water purification and increasing the difficulty of treatment. Patent CN119490268A designs a water purification functional layer, combining it with a ceramic membrane for efficient treatment of manganese-containing groundwater. The ruthenium-iridium-titanium anode and cathode are used to prevent contamination of the water purification functional layer. This method improves the permeability of the functional layer and extends the lifespan of the ceramic membrane through electrochemical cleaning; however, the membrane recovery flux is too low, only 28 L / (m²). 2Patent CN118183943A describes an MXene electroactive membrane with a two-dimensional structure. The MXene electroactive membrane prepared by this method possesses characteristics such as controllable surface thickness, strong hydrophilicity, minimal oxygen evolution side reactions, and the presence of oxygen and titanium vacancies as electrocatalytic active sites, achieving in-situ self-cleaning of membrane fouling. However, during pollutant treatment, the MXene electroactive membrane exhibits a low removal rate of humic acid, only 57.62%, corresponding to a relatively low membrane permeation flux of 247.73 L / (m²). 2 ·h).

[0005] Single-atom catalysts (SACs) have attracted much attention due to their significant catalytic activity resulting from the formation of unsaturated coordination structures with metal centers on solid supports, centered on specific single atoms, and their wide application in heterogeneous catalysis. Patent CN118925802A proposes a method for preparing an iron single-atom composite catalytic membrane, specifically, the fabrication of an Fe-Co dual single-atom catalyst coated with a polytetrafluoroethylene (PVDF) membrane via electrospinning, which effectively degrades antibiotic pollutants. However, this single-atom catalytic membrane exhibits a relatively low membrane flux of only 15 L / (m²). 2 •h) may exacerbate membrane fouling. Patent CN117282281A proposes a method for preparing a confined ceramic membrane using single-atom cobalt-doped carbon material. This method utilizes the nanoscale space provided by the single-atom cobalt-doped reduced graphene oxide catalyst layer and the pores of the ceramic membrane to effectively decompose ozone and accelerate the generation of hydroxyl radicals. However, the preparation process of this single-atom membrane is complex and increases the manufacturing cost.

[0006] It is evident that existing electroactive membranes suffer from problems such as cumbersome operation, poor treatment effect, and low membrane permeation flux. Therefore, there is an urgent need to develop an electroactive membrane that is easy to operate, environmentally friendly, has high and stable pollution removal performance, and can achieve in-situ self-cleaning. Summary of the Invention

[0007] The purpose of this invention is to provide an in-situ self-cleaning cathode single-atom iron-carbon-based electroactive membrane and its preparation method. The cathode single-atom iron-carbon-based electroactive membrane has the advantages of good wastewater treatment effect, high membrane permeation flux, in-situ self-cleaning, and simple preparation process.

[0008] In a first aspect, the present invention provides a cathode single-atom iron-carbon based electroactive membrane, comprising the following components: a membrane substrate and an electroactive layer loaded on its surface; The electroactive layer is a film prepared by reacting a metal-organic framework material and a phosphorus-containing organic reagent as a precursor; its surface has electron-rich active sites with microscopic single-atom iron coordination environment.

[0009] The metal-organic framework material is MIL-88B(Fe); The phosphorus-containing organic reagent is one or more of diphenylphosphine, triphenylphosphine, and tributylphosphine; The mass ratio of the metal-organic framework material to the phosphorus-containing organic reagent is 1:(2-5).

[0010] The cathode single-atom iron-carbon based electroactive film has the following physicochemical characteristics: (1) The average pore size of the single-atom iron-carbon based electroactive membrane is 75-82 nm, and the porosity is 41.2-45.0%; (2) The thickness of the electroactive layer on the membrane surface is 8.1-9.5 μm; (3) Membrane flux is 280-295 L / (m 2 ·h).

[0011] The membrane substrate is a ceramic membrane. Compared with organic membranes (such as polytetrafluoroethylene membranes and polyamide membranes), ceramic membranes have high stability and corrosion resistance.

[0012] Secondly, the present invention provides a method for preparing the above-mentioned cathode single-atom iron-carbon based electroactive film, comprising the following steps: S1. Disperse the metal-organic framework material and phosphorus-containing organic reagent in a solvent, and filter under vacuum to obtain a solid powder. S2. Vacuum dry, pyrolyze, and etch the solid powder to obtain a single-atom iron-carbon based material; S3. Dissolve the obtained single-atom iron-carbon-based material in a mixed solvent to form an emulsion, and then form an electroactive film on the surface of a ceramic membrane by vacuum filtration. S4. A titanium ring is attached to the edge of the ceramic film with the obtained electroactive film by using conductive adhesive to obtain a cathode monatomic iron-carbon-based electroactive film.

[0013] In step S1, the solvent is N,N-dimethylformamide.

[0014] In step S2, the vacuum drying conditions are: vacuum degree of 260-267 Pa, temperature of 30-80℃, preferably 60℃, and time of 10-15 h. The pyrolysis conditions are as follows: temperature 500-800℃, preferably 700℃, time 60-200min, preferably 180min, calcination gas is argon, and heating rate is 1-5℃ / min. The etching is an acid pickling process; the acid is one or more of sulfuric acid, hydrochloric acid, and nitric acid; the etching conditions are: the concentration of the acid solution is 0.5-2 mol / L, the temperature is 60-100℃, preferably 80℃, and the time is 2-6 h, preferably 5 h.

[0015] In step S3, the mixed solvent is composed of water, organic reagents, and perfluorosulfonic acid polymer in a volume ratio of 4:1:(0.025-0.05); The organic reagent is isopropanol or ethanol; The mass ratio of the single-atom iron-carbon-based material to the mixed solvent is 1:(5-10). The ceramic membrane is made of alumina, with an average pore size of 130-132 nm and a porosity of 42.0-45.5%.

[0016] In step S4, the conductive adhesive is a copper / silver conductive adhesive.

[0017] As a specific embodiment of the present invention, the preparation method of the in-situ self-cleaning cathode single-atom iron-carbon-based electroactive film includes the following steps: (1) Provide a metal-organic framework material MIL-88B(Fe) with a porous structure as a precursor; (2) Mix the above MIL-88B(Fe) with triphenylphosphine in a certain proportion, disperse it ultrasonically in N,N-dimethylformamide, and then obtain a yellow solid powder by vacuum filtration; (3) The solid powder obtained in step (2) above is vacuum dried and then calcined at high temperature to obtain black solid powder; (4) The powder obtained in step (3) above is acid-etched at high temperature; (5) After the reaction cools to room temperature, wash the material after acid washing in step (4) with a large amount of deionized water, and collect the black solid powder by vacuum filtration to obtain Fe-SA@PSC material; (6) The Fe-SA@PSC material obtained in step (5) above is dissolved in ultrapure water, organic reagent and perfluorosulfonic acid polymer mixed solvent in different proportions and ultrasonically dispersed to obtain a uniform black emulsion. (7) The emulsion obtained in step (6) above is vacuum filtered onto the surface of a ceramic membrane and then vacuum dried to obtain a Fe-SA@PSC material-supported ceramic membrane; (8) Use copper / silver conductive adhesive to attach the titanium ring to the edge of the Fe-SA@PSC material loaded ceramic film obtained in step (7) above to obtain the Fe-SA@PSC / CM electroactive film.

[0018] Thirdly, the present invention provides a filter reactor for wastewater treatment, comprising: a cathode and an anode; The cathode is the aforementioned cathode monatomic iron-carbon-based electroactive membrane.

[0019] The anode is one or more of titanium mesh, platinum mesh, and carbon felt; The oxygen aeration rate in the filtration reactor is 200-350 mL / min, the distance between the cathode and anode plates is 1.0-2.0 cm, and the current density of the plates is 1.5-6.0 mA / cm². 2 The flow rate is 10-90 mL / min.

[0020] As a specific embodiment of the present invention, the filtration reactor includes: a reactor, an anode, and a cathode; the inlet of the reactor is located at the top of the anode, and the outlet is located at the bottom of the cathode membrane.

[0021] In this invention, the wastewater is wastewater containing organic pollutants such as humic acid (HA) and protein (BSA).

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are: 1. Using the single-atom iron-carbon-based electroactive membrane provided by this invention as the cathode, and operating in continuous flow mode, active oxygen species can be generated in situ under the assistance of an electric field without the addition of any chemical reagents. This enhances the reducing ability of dissolved oxygen in water to be converted into active oxygen species, thereby achieving in-situ mineralization removal of organic pollutants. The mineralization rate of typical humic acid (HA) and protein (BSA) organic pollutants reaches 69.16% and 68.78%, respectively.

[0023] 2. The electroactive membrane provided by this invention serves as a cathode, which inhibits the deposition of negatively charged organic matter in water through electrostatic repulsion, thus helping to alleviate the formation of a fouling layer and enabling the electroactive membrane to perform in-situ self-cleaning of organic pollutants. During continuous operation, the membrane flux recovery rate of HA and BSA reaches 50.0%-60.0%.

[0024] 3. The preparation method of the electroactive membrane provided by the present invention is simple and environmentally friendly, which is conducive to its widespread use. Attached Figure Description

[0025] Figure 1 The images are of the Fe-SA@PSC material; where (a) is the X-ray diffraction pattern and (b) is the extended X-ray absorption fine structure pattern.

[0026] Figure 2 The images are scanning electron microscope (SEM) images of the Fe-SA@PSC / CM membrane; (a) is the external image, (b) is the SEM image of the membrane surface, and (c) is the cross-section.

[0027] Figure 3 This is a schematic diagram of an electro-Fenton oxidation filtration system using Fe-SA@PSC / CM membrane.

[0028] Figure 4The graph shows the removal efficiency of Fe-SA@PSC / CM membrane for HA and BSA under separate filtration and electro-Fenton oxidation filtration.

[0029] Figure 5 The graph shows the membrane flux changes of the Fe-SA@PSC / CM membrane in separate filtration and electro-Fenton oxidation filtration of BSA (a) and HA (b).

[0030] Figure 6 Scanning electron microscope (SEM) images of the Fe-SA@PSC / CM membrane surface after individual filtration and electro-Fenton oxidation filtration for BSA and HA fouling.

[0031] Figure 7 The graphs show the effects of Fe-SA@PSC / CM membrane on treating pharmaceutical wastewater under separate filtration and electro-Fenton oxidation filtration; where (a) is the removal effect graph and (b) is the membrane flux change graph. Detailed Implementation

[0032] The present invention will be further described below with reference to specific embodiments, but the present invention is not limited to the following embodiments.

[0033] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0034] Unless otherwise specified, all reagents, materials, instruments, etc. used in the following examples are commercially available.

[0035] Example 1: Preparation method of single-atom iron-carbon based materials The specific steps are as follows: 1) Weigh 1.0g of MIL-88B(Fe) powder and 2.0g of triphenylphosphine reagent, and add them separately to 150mL of N,N-dimethylformamide solvent. Stir at room temperature for 2 hours until completely mixed and dispersed. Then, filter under vacuum to obtain yellow solid powder MIL-88(B)+P. Place MIL-88(B)+P in a vacuum drying oven at 265Pa and dry at 60℃ for 10 hours. 2) Weigh 1.5g of MIL-88(B)+P and calcine it at high temperature. Set the calcine temperature to 700℃, the calcine time to 180 min, the calcine gas to argon, and the heating rate to 5℃ / min to obtain a black solid powder. 3) Then, weigh 0.2 g of the calcined black solid powder and place it in a 100 mL beaker. Add 80 mL of 2 mol / L H2SO4 and stir continuously at 80 °C for 5 h. After the reaction cools to room temperature, wash the acid-washed material with a large amount of deionized water and collect the sample by vacuum filtration. Finally, place the sample in an oven at 60 °C for 12 h to dry, and obtain the single-atom iron-carbon based material Fe-SA@PSC.

[0036] Characterization results: like Figure 1 As shown in (a), the X-ray diffraction (XRD) results show that the Fe-SA@PSC material has characteristic peaks with diffraction angles of 25.6° and 42.0°, corresponding to the graphite carbon structure of the C(002) and C(100) crystal planes. Compared with the standard card of graphite carbon, no iron oxide species and zero-valent iron were observed.

[0037] like Figure 1 As shown in (b), the extended X-ray absorption fine structure spectrum reveals that Fe-SA@PSC exhibits only one main peak (without phase correction) at approximately ~1.56 Å, located between Fe-C(O) at ~1.45 Å and Fe-P at ~1.67 Å, ​​indicating the coexistence of Fe-C(O) and Fe-P bonds. Simultaneously, scattering of second-shell Fe-C coordination exists at ~2.61 Å. No Fe-Fe coordination at ~2.20 Å and Fe-O coordination at ~1.42 Å is observed, further suggesting that Fe in Fe-SA@PSC may undergo unsaturated coordination with C and P, anchoring isolated atomic sites within the carbon matrix.

[0038] Example 2: Preparation method of cathode single-atom iron-carbon based electroactive film The specific steps are as follows: 1) Weigh 5 mg Fe-SA@PSC and dissolve it in a mixed solution of ultrapure water:isopropanol:perfluorosulfonic acid polymer reagent = 20 mL:5 mL:125 μL. Mix the solution by sonication for 40 min to obtain a uniformly dispersed black emulsion. 2) The black emulsion was vacuum filtered onto the surface of the ceramic membrane and dried in an oven at 80°C for 5 h to obtain the Fe-SA@PSC material-supported ceramic membrane; 3) A titanium ring is bonded to the edge of the Fe-SA@PSC material-supported ceramic film using copper / silver conductive adhesive to obtain the Fe-SA@PSC / CM electroactive film, such as... Figure 2 As shown in (a).

[0039] Characterization results: like Figure 2As shown in (b), a relatively dense electroactive layer is deposited on the surface of the Fe-SA@PSC / CM film. The Fe-SA@PSC material exhibits a spindle-like rod-like morphology, and the thickness of the electroactive layer on the film surface reaches 8.12±0.89μm. Figure 2 As shown in (c).

[0040] Example 3: Application of cathode single-atom iron-carbon based electroactive membrane in the treatment of simulated wastewater The specific steps are as follows: Using the Fe-SA@PSC / CM membrane prepared in Example 2 as the cathode, and one of the following—a titanium mesh, a platinum mesh, or a carbon felt—as the anode, each connected to an external DC power supply, the reactor was placed inside a filter reactor. The reactor inlet was located at the top of the anode, and the outlet was located at the bottom of the cathode membrane. The inlet was connected to an inlet tank via a peristaltic pump, which introduced 150 mL of a 0.05 mol / L sodium sulfate solution and 10 mg / L HA and BSA contaminants into the reactor. A circulating inlet method was used, and the effluent was returned to the inlet tank. The anode and cathode plates were spaced 1.5 cm apart, and the current density of the plates was 5.9 mA / cm². 2 The oxygen aeration rate in the reactor is 250 mL / min, and the flow rate is 40 mL / min. Figure 3 As shown, HA and BSA were selected as model organic pollutants to simulate typical humic acid and protein-based organic pollutants in industrial wastewater.

[0041] Application results: like Figure 4 As shown, the Fe-SA@PSC / CM membrane alone filters UV light from HA and BSA. 254 The removal rates of UVA and TOC were 54.16% and 54.0%, and 46.70% and 47.88%, respectively. When an electric field was applied, electro-Fenton oxidation filtration improved the removal of UVA and TOC from HA and BSA. 254 The removal rates of HA and BSA reached 77.96%, 73.96%, 69.16%, and 68.78%, respectively. This is attributed to the fact that the Fe-SA@PSC / CM membrane generates a large number of active oxygen species in situ at the cathode, which can oxidize the HA and BSA molecules adsorbed on the membrane surface into small molecules and mineralize them into H2O and CO2, thereby achieving efficient oxidation removal of HA and BSA.

[0042] like Figure 5As shown, when the Fe-SA@PSC / CM membrane filters BSA and HA separately, the membrane flux ratio decreases from 1.0 to 0.63 and 0.48, respectively. When an electric field is applied, electro-Fenton oxidation filtration increases the membrane flux ratio by nearly 50.0% and 40.0%, respectively. After hydraulic backwashing, the pure water flux further increases by 30.0% and 40.0%. Compared to BSA, the pure water flux increases significantly after HA backwashing. This is attributed to the fact that HA is negatively charged during the reaction, resulting in strong electrostatic repulsion with the cathode Fe-SA@PSC / CM membrane, thus reducing HA deposition on the cathode membrane surface.

[0043] like Figure 6 As shown, when filtering HA and BSA separately, a relatively dense cross-linked fouling layer was formed on the surface of the Fe-SA@PSC / CM membrane. After applying cathodic electro-Fenton oxidation, a loose and porous fouling layer was formed on the surface of the Fe-SA@PSC / CM membrane. Exposed Fe-SA@PSC material could be observed, and many exposed pores existed. This provides more channels for transporting water molecules and achieves effective recovery of membrane flux.

[0044] Example 4: Application of cathode single-atom iron-carbon based electroactive membrane in the treatment of actual pharmaceutical wastewater The processing device is configured as in Example 3.

[0045] The application results are as follows: like Figure 7 As shown in (a), Fe-SA@PSC / CM individual filtration for UV in pharmaceutical wastewater 254 The removal rates of UV and COD were only 21.5% and 15.46%, respectively. However, after applying an electric field, the UV... 254 The removal rates of both UV and COD increased by nearly 3 times, and UV... 254 The removal rates of COD and COD reached 60.12% and 54.24% respectively, and the effluent quality met the standard of "Water Quality for Industrial Water Reuse of Urban Wastewater" (GB / T 19923-2005), and can be reused for cooling water, washing water and process and product water.

[0046] like Figure 7 As shown in (b), compared with filtering pharmaceutical wastewater alone, the Fe-SA@PSC / CM membrane improved the membrane flux by nearly 25.0% through electro-Fenton oxidation filtration. After physical ultrapure water cleaning and chemical sodium hydroxide solution cleaning, the fouling layer formed on the membrane surface became loose and porous due to in-situ oxidation, which effectively improved the pure water flux. The membrane flux recovery rate reached 90.0%, indicating that the electroactive membrane has excellent self-cleaning performance in treating actual pharmaceutical wastewater.

[0047] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a cathode single-atom iron-carbon based electroactive film, characterized in that, Includes the following steps: 1) Weigh 1.0g of Fe-MIL-88B powder and 2.0g of triphenylphosphine reagent, and add them separately to 150mL of N,N-dimethylformamide solvent. Stir at room temperature for 2 hours until completely mixed and dispersed. Then, filter under vacuum to obtain yellow solid powder Fe-MIL-88B+P. Place Fe-MIL-88B+P in a vacuum drying oven at 265Pa and dry at 60℃ for 10 hours. 2) Weigh 1.5g of Fe-MIL-88B+P and calcine it at high temperature. Set the calcine temperature to 700℃, the calcine time to 180min, the calcine gas to argon, and the heating rate to 5℃ / min to obtain a black solid powder. 3) Then, weigh 0.2 g of the calcined black solid powder and place it in a 100 mL beaker. Add 80 mL of 2 mol / L H2SO4 and stir continuously at 80℃ for 5 h. After the reaction cools to room temperature, wash the acid-washed material with a large amount of deionized water and collect the sample by vacuum filtration. Finally, place the above sample in an oven at 60℃ for 12 h to obtain the single-atom iron-carbon based material Fe-SA@PSC. 4) Weigh 5 mg Fe-SA@PSC and dissolve it in a mixed solution of ultrapure water:isopropanol:perfluorosulfonic acid polymer reagent = 20 mL:5 mL:125 μL. Mix the solution by sonication for 40 min to obtain a uniformly dispersed black emulsion. 5) The black emulsion was vacuum filtered onto the surface of the ceramic membrane and dried in an oven at 80°C for 5 h to obtain the Fe-SA@PSC material-supported ceramic membrane. 6) A titanium ring was attached to the edge of the Fe-SA@PSC material-loaded ceramic film using copper / silver conductive adhesive to obtain the Fe-SA@PSC / CM electroactive film.

2. The cathode single-atom iron-carbon based electroactive film prepared by the method of claim 1.

3. The cathode single-atom iron-carbon based electroactive membrane according to claim 2, characterized in that, It has the following physicochemical characteristics: (1) The average pore size of the single-atom iron-carbon based electroactive membrane is 75-82 nm, and the porosity is 41.2-45.0%; (2) The thickness of the electroactive layer on the membrane surface is 8.1-9.5 μm; (3) Membrane flux is 280-295 L / (m 2 ·h).

4. A filtration reactor for wastewater treatment, characterized in that, It comprises the following components: a cathode and an anode; the cathode is the cathode single-atom iron-carbon-based electroactive membrane as described in claim 2.

5. The filtration reactor according to claim 4, characterized in that, The anode is one or more of titanium mesh, platinum mesh, and carbon felt; The oxygen aeration rate in the filter reactor is 200-350 mL / min, the distance between the cathode and anode plates is 1.0-2.0 cm, and the current density of the plates is 1.5-6.0 mA / cm². 2 The flow rate is 10-90 mL / min.

Citation Information

Patent Citations

  • Monatomic cobalt-doped carbon material confinement ceramic membrane as well as construction method and application thereof

    CN117282281A

  • MXene electroactive membrane for strengthening reverse osmosis concentrated water treatment and preparation method of MXene electroactive membrane

    CN118183943A

  • Fe monatomic composite catalytic membrane as well as preparation method and application thereof

    CN118925802A

  • Manganese removal device and in-situ electrochemical preparation and cleaning method of manganese removal functional layer

    CN119490268A

  • Method for preparing organic / inorganic hybrid electroactivity ion exchange membrane in microgravity environment

    CN105820358A